WHAT STIMULATES SCIENTISTS TO RESEARCH RESULTS COMMERCIALIZATION? DISCOVERY AND DELIVERY SKILLS PERSPECTIVE - Zastempowski, Maciej; Łaskowska, Justyna; Kalocińska-Szumska, Aleksandra (Organizacja i Kierowanie, 2023)
Based on a systematic literature review and the concept of ‘Innovator’s DNA’ by Dyers et al., this paper aims to broaden the knowledge about scientists’ discovery and delivery skills that stimulate them to commercialize research results. We use the data from a quantitative study conducted at one of the leading research universities in Poland. The survey was completed on a representative sample of 496 scientists. We used the EFA to test the factors underlying the Innovator’s DNA scale and the logistic regression to interpret the relationship between the identified scientist’s skills and the commercialization of their results. The EFA results showed that, in the case of scientists, unlike in the Innovator’s DNA concept, the analyzed skills focused on four factors. We defined them as disciplined, detail-oriented implementation, searching for new ideas, drawing inspiration, and questioning skills. The logistic regression estimation showed that only the drawing inspiration skills affected the commercialization activity of the surveyed scientists.